Budgeting in Times of Economic Crisis - Becker, Sebastian D.; Mahlendorf, Matthias D.; Schäffer, Utz; Thaten, Mario (Contemporary Accounting Research, 2016)
Abstract This article examines how corporate reliance on budgets is affected by major changes in the economic environment. We combine survey and archival data from the economic crisis that began in 2008. The results indicate that budgeting became more important for planning and resource allocation but less important for performance evaluation in companies affected more strongly by the 2008 economic crisis. Additional evidence from interviews and data gathered in a focus group further illustrate these results and show the changes organizations have introduced to respond to the economic crisis. Taken together, and contrary to more general conclusions from the literature such as an overall increase or decrease in the importance of budgeting, we find that companies emphasize certain budgeting functions over others during economic crises.